Knowledge and communication difficulties for patients with chronic heart failure: qualitative study. Issue 7261 (9th September 2000) - Rogers, A E; Addington-Hall, J M; Abery, A J; McCoy, A S M; Bulpitt, C; Coats, A J S; Gibbs, J S R
Abstract: Objectives: To explore patients' understanding of chronic heart failure; to investigate their need for information and issues concerning communication. Design: Qualitative analysis of in-depth interviews by a constant comparative approach. Participants: 27 patients identified by cardiology and care of the elderly physicians as having symptomatic heart failure (New York Heart Association functional class of II, III, or IV) and who had been admitted to hospital with heart failure in the past 20 months. Results: Participants were aged 38–94 (mean 69 years); 20 had a New York Heart Association classification of III or IV. All had at least one concurrent illness. Participants sought information from the research interviewer about their heart failure, their prognosis, and likely manner of death. They also described several factors that could inhibit successful communication with their doctors. These included difficulties in getting to hospital appointments, confusion, short term memory loss, and the belief that doctors did not want to provide patients with too much knowledge. Conclusions: Good communication requires the ability both to listen and to impart relevant information. Effective and better ways of communicating with patients with chronic heart failure need to be tested. Disease specific barriers to effective communication, such as short term memory loss, confusion, and fatigue should be addressed. Strategies to help patients ask questions, including those related to prognosis, should be developed.